(untitled) (Journal of the College of Basic Education, 2026)
Our research today focuses on drama, primarily as an art form and secondarily as a literary genre. It encompasses a range of poetic structures and experiences specific to poetry, from the theories of Greek art through modern Western philosophy to contemporary dramatic thought. The research is based on differentiating between dramatic terminology. Among these modern terms are "dramaturgy," the science of drama, and "teatrology," a French term that combines theory with practical application on the stage. This study examines the dramatic function inherent in the artistic formation of literary expression, encompassing both poetic and theatrical aspects. It begins with the premise that a dramatic text is written to be visualized and performed on stage. Furthermore, the term "drama" itself is a critical concept that has evolved over time. Initially, drama was considered the art of the event by the ancient Greeks, and later, through the interplay of various literary schools and movements in Europe, it reached its current form. Our research also explores the relationship between drama and theatrical dialogue, as well as drama and literary criticism. This is based on the understanding that dramatic discourse is a form of critical discourse within both Arab and Western literary criticism, and their interrelationships. The study concludes with two main sections, each providing a separate explanation of the narrative term and the concept of narrative in both Western and Arab contexts.